Tests of skeletal muscle function in children. Issue 3 (March 1978) - Hosking, G P; Young, A; Dubowitz, V; Edwards, R H
Abstract : The contractile properties of a large proximal muscle (quadriceps femoris) and a small distal muscle (adductor pollicis) have been measured in normal children and children with neuromuscular disorders. The method of stimulating the quadriceps femoris to contract, previously evaluated in adults, was found to be acceptable to children. In normal children a number of indices of muscle function were found to be similar to those in adults. A small study of the function of the adductor pollicis using supramaximal stimulation of the ulnar nerve was carried out in boys with Duchenne dystrophy. Decreased contractile force and prolonged relaxation times from a tetanic stimulation were noted in both the proximal and distal muscles of the boys with Duchenne dystrophy.